KEBIJAKAN PENETAPAN HARGA PADA PT. ATRINDO ASIA GLOBAL BANDUNG - Sukmayadi (Coopetition : Jurnal Ilmiah Manajemen, 2019)
This study is to analyze the focus of the problem: Pricing Policy at PT. Atrindo Asia Global Bandung. The purpose of this study was to determine the implementation of the pricing policy, constraints and pricing policy solutions at PT. Atrindo Asia Global Bandung. This study uses a Qualitative Method with an independent variable: Price. The sampling technique used is Purposive Sampling, which is a data source sampling technique with certain considerations. Informants are: Marketing Staff, Service Supervisor. Data analysis using the model of Miles and Huberman with the steps: data collection, data reduction, data presentation, conclusion. The method used to test the validity of the data is the triangulation technique. Based on observations, interviews and data analysis, it was concluded that the implementation of the pricing policy at PT. Atrindo Asia Global Bandung, which sets prices based on satisfaction based pricing, relationship pricing, efficiency pricing, cost based pricing, competition based pricing and demand based pricing. Problems that arise are forgetting or not including all the components of the costs incurred, often setting prices too low. The solution is expected to use a mathematical calculation of the costs incurred so that the costs to be incurred are more systematically arranged Implementation of pricing policies at PT. Atrindo Asia Global is expected to be implemented well so that it is able to achieve the company's targets